Analisis Efektivitas dan Kontribusi Pendapatan Asli Daerah Terhadap Pendapatan Daerah Kabupaten Sleman Tahun 2012-2016 Serta Proyeksi Pada Tahun 2017 dan 2018 - Yuliana Endah Widyaningsih; Wuku Astuti; Kristiana Sri Utami (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2018)
Independence of a region can be seen from the ability of the region to meet its own needs by optimizing the Regional Revenue. Local Revenue (PAD) in Sleman is one of the sources of local revenue, although there are still some other sources of revenue. The purpose of this study is to determine the effectiveness and contribution of PAD Sleman to Sleman Local Revenue for the period 2012-2016 and projected PAD Sleman in 2017-2018. The method used in this research is quantitative. Data obtained from the Office of Revenue and Financial Management Sleman District Year 2012-2016. The process of data processing using the formula of analysis of effectiveness, contribution and trend with the Least Square method. The results show that 1) The highest percentage of PAD effectiveness in 2013 is 150.55% and the lowest of 2014 is 104.35%. 2) The contribution of PAD to Regional Income in Sleman Regency is the largest in 2016 of 30.79% and the lowest of 2012 is 18.93% .3) The projection of PAD in 2017 is 809,970,380,800 and in 2018 is 947,199,851,200.